INTRASEASONAL VARIATIONS OF NEAR-SURFACE ZONAL CURRENT OBSERVED IN THE SOUTH-EASTERN EQUATORIAL INDIAN OCEAN - Iskhaq Iskandar (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Dynamics of intraseasonal variability in the near-surface zonal currents in the southeastern equatorial Indian Ocean is examined through the analysis of the observed currents at 1.5S, 90E and sea surface height (SSH) as well as wind fields along the equator for the period of 23 October 2001 to 3 July 2007. The result demonstrates that the zonal current has energetic intraseasonal variations within the period band of 30–70 days. These oceanic intraseasonal variations are forced by the atmospheric intrasea-sonal disturbances from the west to the central Indian Ocean basin west of the mooring location. The coherence analysis indicates that these intraseasonal zonal currents are coherent with the intraseasonal SSH along the equatorial Indian Ocean. The coherence and lag-correlation analyses agree that these intraseasonal zonal currents are associated with eastward propagating waves with a phase speed falls in the first two vertical modes of baroclinic waves observed in the equatorial Indian Ocean.